Efeitos da prática de natação sobre o controle postural e a aprendizagem de habilidades aquáticas em idosos - Gonçalves, Maria Luísa Bacca (Universidade Federal de São Carlos, 2020)
Worldwide, the number of older people is growing rapidly and it is a direct consequence from fertility rates decline and life expectancy increase the older ages. Thus, its necessary to develop strategies for health promotion, diseases prevention, delaying functional declines and, consequently, enhance quality of life in older people. The regular practice of physical exercises has proved to be an efficient strategy in the improvement of biopsychosocial aspects in older adults, mainly when it involves the execution of new motor skills has been observed. However, few studies have investigated the effects of a period of practice about postural control and the learning of new motor skills in older people (mainly in physically active older people), with no studies in the literature about the effects of swimming practice on postural control and aquatic skills learning in these population. Therefore, the purpose of this dissertation was to investigate the effect of a swimming program of postural control and aquatic swimming skills in physically active older adults. In this sense, two studies were conducted. Study 1, entitled “Effect of swimming practice on postural control in older adults”, aimed to investigate the effects of swimming practice on postural control in older adults”. Participated in Study 1 24 physically active older adults, divided into two groups: Swimming Group (n=12; age: 69,6 ± 4,7 years; weight: 71,0 ± 17,6 kg; height: 1,63 ± 0,09 m) that took part in a swimming program carried out for a period of 12 weeks and consisting of 24 swimming practice sessions; and a Control Group (n=12; age: 64,3 ± 3,7 years; weight: 76,6 ± 12,7 kg; height: 1,67 ± 0,08 m), that didn’t take part in the swimming program. Postural control was assessed before (pre-test) and after (post-test) the intervention using a force platform on which the individuals remained standing, in 8 different experimental conditions that involved manipulations at the base of support, vision and surface in order to check the behavior of the center of pressure. Study 2, entitled “Does a 12-week swimming program promote aquatic skill learning in older adults?”, aimed to investigate the effect of a swimming program on the learning of aquatic skills in older adults. Participated in the Study 2 the older adults who made up the Swimming Group in the Study 1. Aquatic skills were assessed before (pre-test) and after (post-test) the swimming program, and one week after the post-test (retention test) through a checklist (Scale of Swimming Skills) consisting of performance criteria and subdivided into two subtests: adaptation to the aquatic environment and front crawl. In general, the results of Study 1 revealed differences from pre- to post-test in three of the experimental conditions evaluated for the amplitude (maximum – minimum) of the center of pressure displacement, indicating that the Swimming Group benefited from the practice, mainly under more challenging balance conditions when compared to the Group Control. In the Study 2 results revealed increases from pre-test to post-test and retention test for adaptation to the aquatic environment score, front crawl score, and total score of the Scale of Swimming Skills. Based upon these results, it is possible to conclude that a 12-week swimming program, as a new and additional sensorimotor experience to the routine of physically active older people, led to improvement of postural control and the learning of aquatic skills of adaptation to aquatic environment and front crawl, enhancing the positive biopsychosocial effects that physical exercise brings to the older people.
Effects of swimming practice on postural control and aquatic skills learning in the elderly
Keywords: Natação; Controle postural; Aprendizagem motora; Habilidades aquáticas; Idosos; Swimming; Postural control; Motor learning; Aquatic skills; Older adults; CIENCIAS DA SAUDE::EDUCACAO FISICA